Laminated film and method for producing same

JP7638049B1Active Publication Date: 2025-03-03UNITIKA LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024536235
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-02-22
Filing Date
2024-06-10
Publication Date
2025-03-03
Estimated Expiration
2044-06-10

AI Technical Summary

Benefits of technology

【0009】 本発明の積層フィルムは、樹脂層側の表面が平坦性に優れ、良好な離型性を有し、製膜·加工時に適した易滑性を有するため、両面テープや粘着材料の保護フィルム用途、液晶ディスプレイ用部品、プリント配線板などを製造する際の保護材料や工程材料用途、イオン交換膜やセラミックグリーンシート、放熱シートなどのシート状構造体成形用途、など様々な用途に離型フィルムとして好適に用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638049000001
    Figure 0007638049000001
  • Figure 0007638049000002
    Figure 0007638049000002
  • Figure 0007638049000003
    Figure 0007638049000003
Patent Text Reader

Abstract

A laminated film having a resin layer provided on at least one surface of a base film, The surface of the substrate film on which the resin layer is provided is substantially free of particles, The resin layer contains an acid-modified polyolefin resin (A) and a crosslinking agent (C), A laminate film characterized in that the developed interface area ratio (Sdr) of a resin layer surface is 0.025 to 0.304%, and the maximum height (Sz) is 0.01 to 0.50 μm, as measured by a non-contact surface profiler.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film and a method for producing the same. [Background technology]

[0002] Recently, electronic information devices have become smaller and more highly integrated, and process films used in the manufacture of such devices are required to have excellent flatness. Patent Document 1 discloses a slippery film which has a resin layer with good flatness and good slipperiness during film formation and processing and is suitable as a release material.

[0003] The base film constituting the slippery film disclosed in Patent Document 1 contains particles to impart slipperiness. However, since the resin layer is formed on the base film containing particles, the shape of the particles appears on the surface of the resin layer, and there is a risk that this shape will be transferred to the adherend, and there is room for further improvement in order to satisfy the high flatness required for miniaturization of electronic information devices.

[0004] In a laminated film in which a resin layer is formed on a substrate film, if the particle content in the substrate film is reduced or the particle diameter of the particles is made smaller in order to increase the flatness of the resin layer surface, the slipperiness of the substrate film surface tends to decrease. On the other hand, if the particle content in the substrate film is increased to increase the flatness of the substrate film surface, the flatness of the resin layer surface tends to decrease. Thus, it has been difficult to obtain a laminated film that achieves both flatness and slipperiness at a high level. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-020429 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of these problems, the present invention aims to provide a laminated film in which a resin layer provided on a base film exhibits good releasability from an adherend, has excellent flatness that prevents transfer to the adherend, and has excellent lubricity during film formation and processing. [Means for solving the problem]

[0007] As a result of intensive research to solve the above problems, the inventors discovered that by using a liquid for forming a resin layer containing a specific compound to form a resin layer on a substrate film surface that substantially does not contain particles, it is possible to obtain a laminated film that has high levels of both flatness and lubricity and also has good releasability, and thus arrived at the present invention.

[0008] The laminated film of the present invention, in which a resin layer is provided on at least one surface of a base film, is The surface of the substrate film on which the resin layer is provided is substantially free of particles, The resin layer contains an acid-modified polyolefin resin (A) and a crosslinking agent (C), The resin layer surface is characterized in that the developed interface area ratio (Sdr) is 0.025 to 0.304% and the maximum height (Sz) is 0.01 to 0.50 μm, as determined by a non-contact surface shape measuring device. According to the laminated film of the present invention, the olefin component of the acid-modified polyolefin resin (A) preferably contains propylene or 1-octene. According to the laminated film of the present invention, the propylene content in the olefin component is preferably 70% by mass or more. According to the laminated film of the present invention, the content of 1-octene in the olefin component is preferably 15% by mass or more. According to the laminated film of the present invention, the peel strength between the resin layer and the epoxy prepreg is preferably 0.5 N / cm or less. The method for producing a laminated film of the present invention is a method for producing the above-mentioned laminated film, A step of applying a resin layer-forming liquid material, which contains an acid-modified polyolefin resin (A), a crosslinking agent (C), and at least one compound (D) selected from the group consisting of an amphiphilic oligomer, acetylene glycol, and an ethylene oxide adduct of acetylene glycol, and has a liquid temperature of 20 to 40°C, onto a substrate film; A step of drying and stretching the substrate film on which the resin layer-forming liquid has been applied; The present invention is characterized in that it comprises: According to the method for producing the laminated film of the present invention, it is preferable to apply a resin layer-forming liquid material containing 2 to 50 parts by mass of the compound (D) per 100 parts by mass of the acid-modified polyolefin resin (A). Effect of the Invention

[0009] The laminated film of the present invention has an excellent flatness on the surface on the resin layer side, good releasability, and easy slippage suitable for film formation and processing, and therefore can be suitably used as a release film for various applications, such as protective films for double-sided tapes and adhesive materials, protective materials and process materials when producing liquid crystal display parts, printed wiring boards, etc., and molding of sheet-like structures such as ion exchange membranes, ceramic green sheets, and heat dissipation sheets. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The laminated film of the present invention has a resin layer provided on at least one of the surfaces of a substrate film that is substantially free of particles. The resin layer contains an acid-modified polyolefin resin (A) and a crosslinking agent (C), and has a developed interface area ratio (Sdr) of 0.025-0.304% on the resin layer surface as measured by a non-contact surface profiler, and a maximum height (Sz) of 0.01-0.50 μm on the resin layer surface as measured by the non-contact surface profiler.

[0011] <Base film> Examples of the substrate film constituting the laminated film of the present invention include polyester films such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), poly(1,4-cyclohexylene dimethylene terephthalate), and polylactic acid (PLA); polyolefin films such as polypropylene; polystyrene films; polyamide 6, poly-p-xylylene adipamide (MXD6 nylon), polyamide 66, polyamide 46, polyamide 4T, polyamide 6T, polyamide 9T, polyamide 10T, polyamide 11T, polyamide 12T, and polyamide 6I; polycarbonate films; polyacrylonitrile films; polyimide films; and laminates thereof (e.g., polyamide 6 / MXD6 nylon / polyamide 6, polyamide 6 / ethylene-vinyl alcohol copolymer / polyamide 6, polyamide 6 / 6T, polyamide 6 / 6I, and polyamide 6 / 6T / 6I) or mixtures thereof. Polyester films and polyamide films having mechanical strength and dimensional stability are preferred. Here, T represents terephthalic acid, and I represents isophthalic acid. Among them, the base film is preferably a polyethylene terephthalate film from the viewpoint of adhesion to the resin layer, and is preferably a semi-aromatic polyamide film from the viewpoint of heat resistance and adhesion to the resin layer, and is particularly preferably a polyamide 9T film or a polyamide 10T film.

[0012] (polyester resin) The polymerization method of the polyester resin constituting the substrate film is not particularly limited, and examples thereof include transesterification and direct polymerization. Examples of transesterification catalysts include compounds such as oxides and acetates of Mg, Mn, Zn, Ca, Li, Ti, etc. Examples of polycondensation catalysts include compounds such as oxides and acetates of Sb, Ti, Ge, etc. Since the polyester resin after polymerization contains monomers, oligomers, and by-products such as acetaldehyde, it may be subjected to solid-phase polymerization at a temperature of 200° C. or higher under reduced pressure or in an inert gas stream.

[0013] The intrinsic viscosity of the polyester resin is preferably 0.55 to 0.80, more preferably 0.60 to 0.75. If the intrinsic viscosity of the polyester resin is less than the above range, the polyester resin is likely to break during film formation, making it difficult to stably form the film, and the strength of the obtained film is low. On the other hand, if the intrinsic viscosity of the polyester resin exceeds the above range, the shear heat generated during melt extrusion of the resin in the film production process increases, the load on the extruder increases, the production speed has to be sacrificed, and it becomes difficult to control the thickness of the film, so that the productivity of the film decreases. In addition, the obtained film has an increased amount of thermal decomposition and gelation, and the surface defects, foreign matter, and surface coarse protrusions increase. In addition, if the intrinsic viscosity is too high, the polymerization time and polymerization process are long, which is also a factor that increases costs.

[0014] (Semi-aromatic polyamide resin) The semi-aromatic polyamide resin constituting the base film is composed of a dicarboxylic acid component and a diamine component, and has an aromatic component in the dicarboxylic acid component or the diamine component, and is preferably composed of an aromatic dicarboxylic acid component and an aliphatic diamine component.

[0015] (Production of base film) Next, a method for producing the base film will be described. First, a sufficiently dried resin is fed into an extruder, where it is sufficiently plasticized and melted at a temperature above the temperature at which it exhibits fluidity, passed through a filter selected as necessary, and then the molten polymer is discharged in sheet form from a flat die such as a T-die or I-die, and brought into contact with the cooling surface of a moving cooling body such as a cooling roll or steel belt whose temperature is adjusted to below the glass transition temperature (Tg) to obtain an unstretched film. Methods that can be used to cool and solidify the molten polymer discharged in sheet form by bringing it into contact with the moving cooling body include the air knife casting method, electrostatic application method, and vacuum chamber method. The obtained unstretched film is preferably stretched from the viewpoint of improving mechanical properties and heat resistance, that is, uniaxial orientation is performed by a uniaxial stretching method, or biaxial orientation is performed by a biaxial stretching method. The biaxial stretching method is not particularly limited, but flat-type sequential biaxial stretching method, flat-type simultaneous biaxial stretching method, tubular method, etc. can be used. Among them, the flat-type sequential biaxial stretching method is most suitable for stretching polyester films, and the flat-type simultaneous biaxial stretching method is most suitable for stretching semi-aromatic polyamide films.

[0016] In the uniaxial stretching method for polyester films, an unstretched film is stretched in the longitudinal or transverse direction at a stretch ratio of about 2 to 6 times in the temperature range of the Tg of the resin to 50° C. higher than the Tg. In the simultaneous biaxial stretching method, an unstretched film is biaxially stretched to a stretch ratio of about 2 to 4 times in both the longitudinal and transverse directions in a temperature range of from the Tg of the resin to 50° C. higher than the Tg. Before being introduced into the simultaneous biaxial stretching machine, the unstretched film may be subjected to preliminary longitudinal stretching up to about 1.2 times. In the sequential biaxial stretching method, an unstretched film is heated with a heating roll or infrared rays and stretched in the longitudinal direction to obtain a longitudinally stretched film. The longitudinal stretching is preferably performed at a stretching ratio of 2.5 to 4.0 times in a temperature range of Tg to 40°C higher than Tg of the polyester by utilizing the peripheral speed difference between two or more rolls. The longitudinally stretched film is then continuously subjected to transverse stretching in the width direction, heat setting, and heat relaxation in sequence to obtain a biaxially oriented film. The transverse stretching is started at a temperature of Tg to 40°C higher than Tg of the resin, and the maximum temperature is preferably a temperature (100 to 40)°C lower than the melting point (Tm) of the resin. The transverse stretching ratio is adjusted depending on the required physical properties of the final film, but is preferably 3.5 times or more, further preferably 3.8 times or more, and more preferably 4.0 times or more. After stretching in the longitudinal direction and the width direction, the film can be further stretched again in the longitudinal direction and / or the width direction to increase the elastic modulus and dimensional stability of the film. Following the stretching, it is preferable to heat set the film for several seconds at a temperature (50-10)°C lower than the Tm of the resin, and simultaneously relax the film by 1-10% in the width direction. After the heat setting, the film is cooled to below Tg to obtain a biaxially stretched film.

[0017] In stretching the semi-aromatic polyamide film, the flat-type simultaneous biaxial stretching method is optimal because it has good film thickness accuracy and uniform physical properties in the film width direction as described above. As a stretching device for the flat-type simultaneous biaxial stretching method, a screw-type tenter, a pantograph-type tenter, a linear motor-driven clip-type tenter, etc. can be used. The stretching ratio is preferably within the range of 1.5 to 10 times, more preferably 2 to 5 times, in both the longitudinal and transverse directions in order to provide a semi-aromatic polyamide film finally obtained with excellent heat resistance and mechanical strength. The stretching speed is preferably such that the stretching strain rate in both the longitudinal direction and the width direction exceeds 400% / min, more preferably 800 to 12000% / min, and even more preferably 1200 to 6000% / min. If the strain rate is 400% / min or less, crystals grow during stretching and the film breaks, whereas if the strain rate is too fast, the unstretched sheet may be unable to keep up with the deformation and break. The stretching temperature is preferably equal to or higher than the Tg of the semi-aromatic polyamide resin, and more preferably exceeds Tg and is equal to or lower than (Tg+50)° C. If the stretching temperature is lower than Tg, the film is likely to break and stable production cannot be performed, whereas if the temperature exceeds (Tg+50)° C., uneven stretching may occur. After the semi-aromatic polyamide film is stretched as described above, it is preferable to perform a heat setting treatment as necessary while the film is held by the clips used during stretching. The heat setting temperature is preferably 250 to (Tm-5)°C, more preferably 280 to (Tm-10)°C. If the heat setting temperature is less than 250°C, the resin layer containing the acid-modified olefin resin provided on the semi-aromatic polyamide film before stretching will undergo an insufficient curing reaction, resulting in reduced releasability. Furthermore, after the heat setting treatment, the film is preferably subjected to a relaxation treatment of 1 to 10%, more preferably 3 to 7%, as necessary while still being held by the clips. By performing the relaxation treatment, the film can obtain sufficient dimensional stability. After optionally performing heat setting or relaxation treatment, the film is cooled and wound on a take-up roll to obtain a semi-aromatic polyamide resin stretched film roll. The obtained semi-aromatic polyamide resin stretched film roll can be slit to a desired width.

[0018] (Multi-layered base film) By the above-mentioned production method, a substrate film having a single layer structure can be obtained, but the substrate film may also be a film having a multilayer structure in which two or more kinds of layers are laminated. The multilayer film can be produced by the above-mentioned production method, in which the resins constituting each layer are melted separately, extruded using a multilayer die, laminated and fused before solidification, and then biaxially stretched and heat-set, or by a method in which two or more resins are melted separately, extruded to form films, and laminated and fused in an unstretched state or after stretching, etc. From the viewpoint of process simplicity, it is preferable to use a multilayer die and laminate and fused before solidification.

[0019] In the present invention, the substrate film may be a single layer or a multilayer (e.g., two-type two-layer, two-type three-layer, three-type three-layer, four-layer or more multilayer, etc.) as described above, but is preferably a multilayer from the viewpoint of being able to control the surface roughness for each side and improving handling properties such as winding properties. Two-type two-layer and two-type three-layer configurations are more preferred, and two-type two-layer is even more preferred. The two-type two-layer configuration refers to a two-layer configuration manufactured using two types of layer-forming materials, and these two layers have different compositions (e.g., particle content). The two-type three-layer configuration refers to a three-layer configuration manufactured using two types of layer-forming materials, and the two outermost layers and the middle layer have different compositions (e.g., particle content). The three-type three-layer configuration refers to a three-layer configuration manufactured using three types of layer-forming materials, and these three layers have different compositions (e.g., particle content).

[0020] (particle) The base film may contain particles for the main purpose of providing easy slippage and preventing scratches in each process. However, the base film constituting the laminated film of the present invention must be substantially free of particles on the side on which the resin layer is laminated. Since the surface of the base film on which the resin layer is formed is substantially free of particles, the surface of the resin layer on which the resin layer containing the specific acid-modified polyolefin resin (A) and the crosslinking agent (C) described later is formed has excellent flatness. On the other hand, each layer of the base film other than the surface on which the resin layer is formed may contain particles within a range that does not impair the effects of the present invention. Note that "substantially free of particles" means that the surface on which the resin layer of the base film is formed is manufactured without adding particles. Therefore, it is particularly preferable that the particle content of the base film surface on which the resin layer is formed is zero, but it may be 0.001% by mass or less, more preferably 0.0005% by mass or less, within a range that does not impair the effects of the present invention.

[0021] The type of particles contained in the substrate film is not particularly limited as long as the particles are capable of imparting slipperiness, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the manufacturing process of the resin constituting the substrate can also be used.

[0022] The shape of the particles is not particularly limited, and may be any of spherical, blocky, rod-like, flat, etc. There are no particular limitations on the hardness, specific gravity, color, etc. of the particles. Two or more types of particles may be used in combination as necessary. The average particle size of the particles is preferably 5 μm or less, more preferably in the range of 0.01 to 3 μm. If the average particle size exceeds 5 μm, the surface roughness of the base film becomes too high, and for example, when used for transfer, the surface shape of the molding surface to be transferred may be affected.

[0023] The particle content in the base film is usually 5% by mass or less, and preferably in the range of 0.0003 to 3% by mass. If the particle content exceeds 5% by mass, the film may be easily broken during the stretching step in the production of the laminated film of the present invention.

[0024] The method of adding the particles is not particularly limited, and a conventionally known method can be adopted. For example, the particles can be added at any stage of producing the resin constituting each layer. In the case of the process of producing a polyester, it is preferable to add the particles after the completion of the esterification or transesterification reaction.

[0025] (Additives) The base film may contain additives, as necessary, such as antioxidants, heat stabilizers, ultraviolet absorbers, antistatic agents, pinning agents, etc. Examples of antioxidants include hindered phenol compounds and hindered amine compounds, examples of heat stabilizers include phosphorus compounds, and examples of ultraviolet absorbers include benzophenone compounds and benzotriazole compounds.

[0026] (Thickness) The thickness of the substrate film is not particularly limited as long as it is within a range that allows formation of a film, but from the standpoints of mechanical strength, handling properties, productivity, etc., it is usually 5 to 300 μm, and preferably 10 to 150 μm.

[0027] <Resin layer> The laminated film of the present invention is a film in which a resin layer is provided on at least one side of the layer of the above-mentioned base film that does not substantially contain particles. The resin component constituting the resin layer is an acid-modified polyolefin resin (A) from the viewpoint of imparting good releasability to the resin layer, and it is necessary that the resin layer further contains a crosslinking agent (C). The resin layer can be formed by applying a liquid for forming a resin layer that contains the acid-modified polyolefin resin (A), the crosslinking agent (C), and at least one compound (D) selected from the group consisting of an amphiphilic oligomer, acetylene glycol, and an ethylene oxide adduct of acetylene glycol.

[0028] (Acid-modified polyolefin resin (A)) The acid-modified polyolefin resin is a resin containing an olefin component as a main component and modified with an acid-modifying component. The resin layer may contain two or more kinds of acid-modified polyolefin resins (A). The olefin component constituting the acid-modified polyolefin resin can be at least one selected from ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 1-nonene.

[0029] From the viewpoint of releasability from the acrylic adhesive, the olefin component more preferably contains ethylene. From the viewpoint of further improving the releasability from the acrylic adhesive, the ethylene content in the olefin component is preferably 50 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more.

[0030] From the viewpoint of releasability from epoxy resin, the olefin component more preferably contains propylene. From the viewpoint of further improving releasability from epoxy resin, the content of propylene in the olefin component is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and most preferably 95% by mass or more.

[0031] From the viewpoint of improving lubricity, the olefin component preferably contains an olefin component having 6 or more carbon atoms, such as 1-hexene, 1-octene, or 1-nonene, and more preferably contains 1-octene. From the viewpoint of further improving lubricity, the content of 1-octene in the olefin component is preferably 15% by mass or more, and more preferably 25% by mass or more.

[0032] From the viewpoint of improving flatness, which is the object of the present invention, the olefin component constituting the acid-modified polyolefin resin preferably has a 1-butene or 1-pentene content of 20 mass% or less, more preferably 15 mass% or less, and even more preferably 10 mass% or less, of the polyolefin component, and it is particularly preferable that the resin does not contain 1-butene or 1-pentene.

[0033] The acid-modified component constituting the acid-modified polyolefin resin includes unsaturated carboxylic acid components, specifically acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, crotonic acid, etc., as well as half esters and half amides of unsaturated dicarboxylic acids. Among them, in order to stably disperse the resin in the aqueous dispersion of the resin described later, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and acrylic acid, methacrylic acid, and maleic anhydride are particularly preferred. Two or more of these acid-modified components may be contained in the acid-modified polyolefin resin.

[0034] The proportion of the acid-modified component in the acid-modified polyolefin resin is preferably 1 to 10% by mass, more preferably 2 to 9% by mass. When the proportion of the acid-modified component is less than 1% by mass, the proportion of polar groups in the acid-modified polyolefin resin contained in the resin layer is reduced, so that the resin layer tends not to have sufficient adhesion to the base film, and may contaminate the adherend released from the resin layer. Furthermore, in the aqueous dispersion of the resin described below, it tends to be difficult to stably disperse the resin. On the other hand, when the proportion of the acid-modified component exceeds 10% by mass, the proportion of polar groups increases, so that the adhesion between the resin layer and the base film is sufficient, but the adhesion between the resin layer and the adherend also increases at the same time, so that the releasability from the adherend tends to decrease.

[0035] In order to further improve the adhesion to the base film, the acid-modified polyolefin resin may contain an ethylenically unsaturated component containing an oxygen atom in the side chain. Examples of ethylenically unsaturated components containing oxygen atoms in the side chain include esters of (meth)acrylic acid and alcohols having 1 to 30 carbon atoms, and among these, from the viewpoint of availability, esters of (meth)acrylic acid and alcohols having 1 to 20 carbon atoms are preferred. Specific examples of such compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. A mixture of these may be used. Among these, from the viewpoint of adhesion to polyester film, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl acrylate, and octyl acrylate are more preferred, ethyl acrylate and butyl acrylate are even more preferred, and ethyl acrylate is particularly preferred. "(meth)acrylic acid" means "acrylic acid or methacrylic acid". The ethylenically unsaturated component containing an oxygen atom in the side chain has a polar group in the molecule, similar to the acid-modified component. Therefore, by including an ethylenically unsaturated component containing an oxygen atom in the side chain in the acid-modified polyolefin resin, the resin layer has high adhesion to the base film. However, if the amount of the ethylenically unsaturated component containing an oxygen atom in the side chain is too large, the properties of the resin derived from the olefin may be lost, and the releasability of the resin layer from the adherend may be reduced. The ratio of the ethylenically unsaturated component containing an oxygen atom in the side chain in the acid-modified polyolefin resin is preferably 1 to 40 mass%, more preferably 2 to 35 mass%, even more preferably 3 to 30 mass%, and particularly preferably 6 to 18 mass%. Even if an acid-modified polyolefin resin containing an ethylenically unsaturated component containing an oxygen atom in the side chain is used, the releasability of the resin layer is not impaired in addition to the adhesion to the substrate film.

[0036] The acid-modified polyolefin resin may be copolymerized with a small amount of other monomers, such as dienes, (meth)acrylonitrile, vinyl halides, vinylidene halides, carbon monoxide, and sulfur dioxide.

[0037] The components constituting the acid-modified polyolefin resin may be copolymerized in the acid-modified polyolefin resin in any form, and examples of the copolymerization state include random copolymerization, block copolymerization, and graft copolymerization (graft modification).

[0038] The melting point of the acid-modified polyolefin resin is preferably 80 to 200° C., and more preferably 90 to 150° C. If the melting point of the acid-modified polyolefin resin exceeds 200° C., high-temperature treatment may be required when forming a resin layer on the surface of the substrate film. On the other hand, if the melting point of the acid-modified polyolefin resin is less than 80° C., the releasability of the resin layer may decrease.

[0039] Examples of acid-modified polyolefin resins that can be used in the present invention include the Bondine series manufactured by Arkema, the Nucrel series manufactured by Mitsui DuPont Polychemicals, the Rexpearl series manufactured by Japan Polyethylene Corporation, the Umex series manufactured by Sanyo Chemical Industries, Ltd., the Bestplast series manufactured by Evonik, the Primacol series and Affinity series manufactured by Dow Chemical Company, the Admer series manufactured by Mitsui Chemicals, Inc., and the Toyotack series manufactured by Toyobo Co., Ltd.

[0040] (Polyvinyl alcohol (B)) In the present invention, the resin layer preferably contains polyvinyl alcohol from the viewpoint of improving releasability. The polyvinyl alcohol is not particularly limited, but examples thereof include a polymer of vinyl ester completely or partially saponified. By containing polyvinyl alcohol in the resin layer, it is possible to improve the adhesion between the resin layer and the substrate film, and also to improve the releasability between the resin layer and the adherend. The polyvinyl alcohol in the present invention is preferably water-soluble in order to be used as a liquid material as described later.

[0041] From the viewpoints of the surface flatness of the resin layer and releasability in a high temperature range, the polyvinyl alcohol preferably has a saponification degree of 90% or more, and more preferably 93% or more.

[0042] The content of polyvinyl alcohol is preferably 10 to 1000 parts by mass, more preferably 100 to 1000 parts by mass, even more preferably 210 to 800 parts by mass, and particularly preferably 300 to 600 parts by mass, per 100 parts by mass of the above resin, from the viewpoints of improving releasability between the resin layer and the adherend and suppressing transfer to the adherend after peeling.

[0043] Examples of polyvinyl alcohol that can be used in the present invention include products manufactured by Japan Vinyl Acetate & Poval Corporation such as "JP-15," "JT-05," "JL-05E," "JM-33," "JM-17," "JF-05," and "VC-10," and products manufactured by Kuraray Co., Ltd. such as "Kuraray Poval" products such as "PVA-CST," "PVA-624," "PVA-203," "PVA-220," and "PVA-405."

[0044] (Crosslinking agent (C)) In the present invention, the resin layer needs to contain a crosslinking agent together with the acid-modified polyolefin resin in order to provide good releasability. By containing the crosslinking agent, the components of the resin layer are crosslinked to improve the releasability, the cohesive force of the resin layer is improved, the resin layer is less likely to transfer to the adherend, and the water resistance is improved.

[0045] The content of the crosslinking agent is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 2 to 10 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin resin. If the content of the crosslinking agent is less than 1 part by mass, the resin layer tends to have a weak cohesive force, poor adhesion to the substrate film, and easily transfer to the adherend. On the other hand, if the content exceeds 20 parts by mass, the resin layer may react with the adherend and have poor releasability, or the liquid material for forming the resin layer may thicken and lose stability.

[0046] As the crosslinking agent, a compound having a plurality of functional groups in the molecule that react with a carboxyl group can be used, and examples thereof include polyfunctional epoxy compounds; polyfunctional isocyanate compounds; polyfunctional aziridine compounds; carbodiimide group-containing compounds; oxazoline group-containing compounds; phenolic resins; and amino resins such as urea compounds, melamine resins, and benzoguanamine resins. One of these may be used, or two or more may be used in combination. Among these, polyfunctional isocyanate compounds, melamine resins, urea compounds, polyfunctional epoxy compounds, carbodiimide group-containing compounds, and oxazoline group-containing compounds are preferred, carbodiimide group-containing compounds and oxazoline group-containing compounds are more preferred, and oxazoline group-containing compounds are even more preferred. By using an oxazoline group-containing compound, it is possible to obtain a laminated film that is excellent in releasability from the adherend and adhesion to the substrate film. These crosslinking agents may also be used in combination.

[0047] Specifically, polyepoxy compounds, diepoxy compounds, etc. can be used as the polyfunctional epoxy compounds. For example, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether can be used as the polyepoxy compounds. For example, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether can be used as the diepoxy compounds.

[0048] Examples of polyfunctional isocyanate compounds that can be used include tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, metaxylylene diisocyanate, hexamethylene-1,6-diisocyanate, 1,6-diisocyanatehexane, an adduct of tolylene diisocyanate and hexanetriol, an adduct of tolylene diisocyanate and trimethylolpropane, polyol-modified diphenylmethane-4,4'-diisocyanate, carbodiimide-modified diphenylmethane-4,4'-diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-bitrylene-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, and metaphenylene diisocyanate. Blocked isocyanate compounds in which the isocyanate groups are blocked with bisulfites and sulfonic acid group-containing phenols, alcohols, lactams, oximes, active methylene compounds, and the like may also be used. An example of a commercially available polyfunctional isocyanate compound is "Basonate HW-100" manufactured by BASF.

[0049] As the polyfunctional aziridine compound, for example, N,N'-hexamethylene-1,6-bis-(1-aziridinecarboxamide), trimethylolpropane-tri-β-aziridinylpropionate, etc. can be used.

[0050] The carbodiimide group-containing compound is not particularly limited as long as it has one or more carbodiimide groups in the molecule. The carbodiimide compound forms an ester with two carboxyl groups in the acid-modified portion of the acid-modified polyolefin resin at one carbodiimide portion to achieve crosslinking. For example, compounds having carbodiimide groups such as p-phenylene-bis(2,6-xylylcarbodiimide), tetramethylene-bis(t-butylcarbodiimide), and cyclohexane-1,4-bis(methylene-t-butylcarbodiimide), and polycarbodiimide, which is a polymer having a carbodiimide group, can be used. One or more of these can be used. Among these, polycarbodiimide is preferred because of its ease of handling. Commercially available polycarbodiimide products include the Carbodilite series manufactured by Nisshinbo Chemical Co., Ltd., specifically, water-soluble types "SV-02", "V-02", "V-02-L2", and "V-04"; emulsion types "E-01" and "E-02"; organic solution types "V-01", "V-03", "V-07", and "V-09"; and solvent-free type "V-05".

[0051] The oxazoline group-containing compound is not particularly limited as long as it has two or more oxazoline groups in the molecule. In the oxazoline compound, each of the two oxazoline moieties forms an amide ester with one carboxyl group in the acid-modified portion of the acid-modified polyolefin resin to achieve crosslinking. Such a polymer can be prepared by polymerization of an addition-polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition-polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline. The addition-polymerizable oxazoline group-containing monomer can be one of these or a mixture of two or more of them. Among these, 2-isopropenyl-2-oxazoline is industrially easily available and is suitable.The other monomer is not limited as long as it is a monomer copolymerizable with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl acrylate and alkyl methacrylate (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salt, potassium salt, ammonium salt, tertiary amine salt, and the like); unsaturated nitriles such as acrylonitrile and methacrylonitrile; acrylamide, methacrylamide, N-alkane, etc. Examples of the monomer include unsaturated amides such as alkyl acrylamide, N-alkyl methacrylamide, N,N-dialkyl acrylamide, and N,N-dialkyl methacrylate (the alkyl group is a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a 2-ethylhexyl group, and a cyclohexyl group); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated aliphatic monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. As the other monomer, one or more of these monomers can be used. Among these, oxazoline group-containing polymers are preferred from the viewpoint of ease of handling. Commercially available oxazoline group-containing polymers include the Epocross series manufactured by Nippon Shokubai Co., Ltd., specifically water-soluble types "WS-500" and "WS-700"; emulsion types "K-1010E", "K-1020E", "K-1030E", "K-2010E", "K-2020E", and "K-2030E".

[0052] As the phenolic resin, for example, resol type phenolic resins and / or novolac type phenolic resins prepared using phenol, bisphenol A, alkylphenols such as pt-butylphenol, octylphenol, and p-cumylphenol, p-phenylphenol, cresol, and the like as raw materials can be used.

[0053] As the urea resin, for example, dimethylol urea, dimethylol ethylene urea, dimethylol propylene urea, tetramethylol acetylene urea, 4-methoxy 5-dimethyl propylene urea dimethylol can be used.

[0054] The melamine resin is, for example, a compound having an imino group, a methylol group, and / or an alkoxymethyl group (e.g., a methoxymethyl group, a butoxymethyl group) as a functional group in one molecule. As the melamine resin, imino group-type methylated melamine resin, methylol group-type methylated melamine resin, methylol group-type methylated melamine resin, fully alkylated methylated melamine resin, etc. can be used. In order to promote the thermal curing of the melamine resin, it is preferable to use an acid catalyst such as p-toluenesulfonic acid.

[0055] As the benzoguanamine resin, for example, trimethylolbenzoguanamine, hexamethylolbenzoguanamine, trismethoxymethylbenzoguanamine, hexakismethoxymethylbenzoguanamine, etc. can be used.

[0056] (Compound (D)) The resin layer in the present invention can be formed using a liquid material for forming a resin layer that contains a resin component and a compound (D). By adding the compound (D) to the liquid material for forming the resin layer and forming the resin layer by a specific method, it is possible to achieve both flatness and easy lubricity in the resin layer. The compound (D) is at least one compound selected from the group consisting of amphiphilic oligomers, acetylene glycol, and ethylene oxide adducts of acetylene glycol. An amphiphilic oligomer refers to an oligomer having both a hydrophobic structure (also called a hydrophobic segment) and a hydrophilic structure (also called a hydrophilic segment) in the molecule. The hydrophobic segment is not particularly limited, but examples thereof include an alkyl group, an alkenyl group, an alkylphenyl group, a perfluoroalkyl group, a perfluoropolyether group, etc. These may be contained alone or may have a structure in which a plurality of them are combined. The hydrophilic segment is not particularly limited, but examples thereof include polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol; and polyhydric alcohols such as glycerin, sorbitol, sorbitan, polyglycerin, fructose, sucrose, glucose, and maltose. Specific examples of acetylene glycol include 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol, 5,8-dimethyl-6-dodecyne-5,8-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 4,7-dimethyl-5-decyne-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 3,6-diethyl-4-octyne-3,6-diol, and 2,5-dimethyl-3-hexyne-2,5-diol. Examples of the ethylene oxide adduct of acetylene glycol include ethylene oxide adducts of the compounds listed as specific examples of acetylene glycol.

[0057] The compound (D) is preferably one that dissolves in 100 g of water at 20° C. in an amount of 0.05 g or more, or one that disperses when 0.1 g of the compound (D) is added to 100 g of water at 20° C. and stirred. If the compound (D) dissolves in an amount of less than 0.05 g or is not dispersible in water, it will not mix with the liquid material for forming a resin layer and will separate over time, and not only will the liquid material for forming a resin layer have poor stability, but the formed resin layer will tend to have a poor appearance.

[0058] The content of the compound (D) in the liquid material for forming a resin layer is preferably 2 to 50 parts by mass, more preferably 3.5 to 30 parts by mass, and even more preferably 5 to 25 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin resin (A). If the content of the compound (D) in the liquid material for forming a resin layer is less than 2 parts by mass, it may be difficult to obtain a resin layer surface having a developed interface area ratio (Sdr) of 0.025 to 0.304% as determined by a non-contact surface profiler. On the other hand, if the content of the compound (D) exceeds 50 parts by mass, the resin layer may have reduced releasability, or interference patterns may appear, or flatness may decrease, and the maximum height (Sz) may not satisfy 0.01 to 0.50 μm. Depending on the type, the compound (D) in the resin layer-forming liquid may volatilize during heat treatment after application to the substrate film, and may not remain in the formed resin layer.

[0059] Examples of commercially available products that can be used as compound (D) in the present invention include, as an amphiphilic oligomer, the Polyflow series "KL-900" manufactured by Kyoeisha Chemical Co., Ltd., as an acetylene glycol, the Olfin series "D-10" manufactured by Nissin Kogyo Co., Ltd., as an ethylene oxide adduct of acetylene glycol, the Olfin series "E1004", "E1006", and "E1010" manufactured by Nissin Kogyo Co., Ltd., as well as the Surfynol series "420", "440", and "485", etc.

[0060] In the present invention, the resin layer may contain a lubricant within a range that does not impair the effects of the present invention. Examples of the lubricant include inorganic particles such as calcium carbonate, magnesium carbonate, calcium oxide, zinc oxide, magnesium oxide, silicon oxide, sodium silicate, aluminum hydroxide, iron oxide, zirconium oxide, barium sulfate, titanium oxide, tin oxide, antimony trioxide, carbon black, and molybdenum disulfide, organic particles such as acrylic crosslinked polymers, styrene crosslinked polymers, silicone resins, fluororesins, benzoguanamine resins, phenolic resins, nylon resins, and polyethylene wax, and surfactants.

[0061] <Liquid for forming resin layer> In the present invention, the liquid medium constituting the resin layer-forming liquid material containing the acid-modified polyolefin resin (A), the crosslinking agent (C) and the compound (D) is preferably an aqueous medium. The aqueous medium means a solvent containing water and an amphipathic organic solvent and having a water content of 2% by mass or more, and may be water alone. An amphipathic organic solvent refers to an organic solvent in which the solubility of water in the organic solvent at 20°C is 5 mass% or more (the solubility of water in organic solvents at 20°C is described in literature such as "Solvent Handbook" (Kodansha Scientific, 10th edition, 1990)). Specific examples of amphipathic organic solvents include alcohols such as methanol, ethanol, n-propanol, and isopropanol; ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone and methyl ethyl ketone; esters such as methyl acetate, n-propyl acetate, isopropyl acetate, methyl propionate, ethyl propionate, and dimethyl carbonate; ethylene glycol derivatives such as ethylene glycol n-butyl ether; organic amine compounds containing ammonia such as diethylamine, triethylamine, diethanolamine, triethanolamine, N,N-dimethylethanolamine, and N,N-diethylethanolamine; and lactams such as 2-pyrrolidone and N-methyl-2-pyrrolidone.

[0062] The solid content concentration of the liquid material for forming the resin layer is not particularly limited and can be appropriately selected depending on lamination conditions, the desired thickness and performance, etc. However, in order to maintain the viscosity of the liquid material at an appropriate level and form a uniform resin layer, the solid content is preferably 2 to 30% by mass, and more preferably 3 to 20% by mass. The liquid material for forming the resin layer may contain additives such as antioxidants, ultraviolet absorbers, lubricants, and colorants, provided that the properties of the liquid material are not impaired.

[0063] <Manufacturing of laminated film> The method for producing a laminated film of the present invention includes a step of applying a liquid material for forming a resin layer to a substrate film, and drying and stretching the applied substrate film. In order to obtain a resin layer surface having a developed interface area ratio (Sdr) as specified in the present invention, the liquid temperature during application of the liquid material for forming a resin layer must be 20 to 40°C, and is preferably 25 to 35°C. If the liquid temperature during application of the liquid material for forming a resin layer is less than 20°C, it becomes difficult to apply the liquid material for forming a resin layer uniformly due to increased viscosity, and the maximum height (Sz) of the resin layer surface may become high. On the other hand, if the liquid temperature during application of the liquid material for forming a resin layer exceeds 40°C, bumping is likely to occur during drying of the resin layer, and the developed interface area ratio (Sdr) of the resin layer surface may become high. Methods for applying the liquid material for forming a resin layer to the substrate film include known methods such as gravure roll coating, reverse roll coating, wire bar coating, lip coating, air knife coating, curtain flow coating, spray coating, dip coating, and brush coating. The liquid material for forming a resin layer is particularly effective in the case of gravure roll coating, since it can suppress the occurrence of coating streaks.

[0064] The method for producing the laminated film of the present invention includes a step of applying a liquid material for forming a resin layer during the production process of a substrate film, and a step of drying and stretching the substrate film together with the liquid material. It is preferable that the method further includes a step of performing an orientation stretching or a heat setting treatment. By applying the resin layer-forming liquid during the manufacturing process of the base film, the resin layer can be formed with a small degree of oriented crystallization on the surface of the base film, improving the adhesion between the base film and the resin layer. In addition, since the resin layer can be heat-treated at a higher temperature while the base film is in a tensed state, the releasability and residual adhesive strength can be improved without deteriorating the quality of the base film. For reasons of simplicity and operational feasibility, it is preferable to employ a sequential biaxial stretching method in which the liquid is applied to a substrate film that has been stretched in a uniaxial direction, the substrate film to which the liquid has been applied is dried, and then the substrate film is further stretched in a direction perpendicular to the uniaxial direction and heat-treated.

[0065] <Characteristics of the resin layer> In the laminated film of the present invention, from the viewpoint of imparting easy slippage and suppressing transfer to the adherend, the developed interface area ratio (Sdr) of the resin layer surface determined by a non-contact surface profiler must be 0.025 to 0.304%, preferably 0.03 to 0.30%, and more preferably 0.04 to 0.25%. If the developed interface area ratio (Sdr) of the resin layer surface is less than 0.025%, the air layer contained in the resin layer surface is very small, resulting in insufficient easy slippage, which causes problems in winding, rewinding, slitting, etc. during the film manufacturing process, causing scratches on the surface, and causing a loss in the appearance of the wound roll. If the developed interface area ratio (Sdr) of the resin layer surface exceeds 0.304%, the unevenness of the resin layer surface becomes large and the flatness is impaired, making it difficult to meet the flatness required for small electronic devices, etc. On the other hand, the developed interface area ratio (Sdr) of the substrate film surface not provided with the resin layer, determined by a non-contact surface profiler, is preferably 0.20% or more. If the developed interface area ratio (Sdr) of the substrate film surface not provided with the resin layer is less than 0.20%, the slipperiness decreases, and processing of the film may become difficult when the film is used for various processes.

[0066] In the present invention, the surface of the resin layer constituting the laminate film must have a surface roughness parameter maximum height (Sz) of 0.01 to 0.50 μm, preferably 0.01 to 0.40 μm, and more preferably 0.01 to 0.20 μm, from the viewpoint of suppressing the transfer of surface properties to the adherend. By having the surface roughness of the resin layer within the above range, the resin layer is flattened, and the transfer of coarse protrusions of the resin layer to the adherend is suppressed.

[0067] In the laminated film of the present invention, the peel strength between the resin layer and the epoxy prepreg, measured by attaching the epoxy prepreg to the resin layer, is preferably 0.01 to 0.5 N / cm, more preferably 0.01 to 0.35 N / cm, and even more preferably 0.01 to 0.15 N / cm. If the peel strength exceeds 0.5 N / cm, peeling is heavy, making it difficult to practically use the film as a release film.

[0068] In the laminated film of the present invention, when an acrylic adherend as a pressure-sensitive adhesive material is attached to the resin layer and measured, the peel strength between the resin layer and the adherend is preferably 3.0 N / cm or less, more preferably 2.8 N / cm or less, and even more preferably 2.6 N / cm or less. If the peel strength exceeds 3.0 N / cm, the peeling is heavy and it becomes difficult to practically use the film as a release film.

[0069] In the present invention, the thickness of the resin layer is preferably 0.01 to 1 μm, more preferably 0.03 to 0.7 μm, and further preferably 0.05 to 0.5 μm. If the thickness of the resin layer is less than 0.01 μm, sufficient releasability cannot be obtained, and if it exceeds 1 μm, it is likely to transfer to the adherend and costs will increase, which is not preferable. EXAMPLES

[0070] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. The properties of the laminated film were measured by the following methods.

[0071] (1) Flatness (developed interface area ratio (Sdr), maximum height (Sz)) Using a non-contact surface profiler (Hitachi High-Tech VS1800), the developed interface area ratio (Sdr) and maximum height (Sz) were measured for the resin layer surface, and the developed interface area ratio (Sdr) was measured for the surface of the base film where the resin layer was not provided, in accordance with ISO 25178. Measurements were performed at 10 points on each layer surface, and the average value was used as the measurement result. (Measurement conditions) Objective lens: 50x ·Measurement area: 112μm×112μm Measurement mode: WAVE (Analysis conditions) Surface correction: 4th order

[0072] (2) Slipperiness (dynamic friction coefficient (μd)) Using a tensile tester (Shimadzu EZ-LX) in accordance with JIS K7125, the dynamic friction coefficient (μd) between the resin layer surface and the surface of the base film on which the resin layer was not provided was determined and evaluated according to the following criteria. Measurements were performed at five locations, and the average value was used as the measurement result. Excellent: Less than 0.25 Good: 0.25 or more, less than 0.30 Acceptable: 0.30 or more, less than 0.40 Impossible: 0.40 or more

[0073] (3) Releasability (peel strength) against epoxy prepreg Both sides of an epoxy prepreg (EI-6765 manufactured by Sumitomo Bakelite Co., Ltd.) measuring 60 mm x 100 mm were sandwiched between the resin layer sides of the laminated film obtained, and the temperature was raised from 30°C to 150°C at a rate of 15°C / min in a vacuum press at 1.07 kPa (8 Torr), and after holding at 150°C for 22 minutes, the temperature was further raised to 190°C at a rate of 5°C / min and then compressed under a pressure of 5 kg / cm. 2 After applying a pressure of 15kg / cm for 10 minutes, 2 The sample was then cooled to room temperature and held at 190°C for 70 minutes while applying a pressure of 1.0 MPa. The peel strength between the cured epoxy prepreg and the laminated film of the obtained sample was measured using a tensile tester (Shimadzu Corporation Autograph AGX-V) in a thermostatic room at 23°C, with a peel angle of 180° and a peel speed of 300 mm / min. Measurements were performed at five locations, and the average value was recorded as the measurement result.

[0074] (4) Releasability (peel strength) for acrylic adhesives A 50 mm wide, 150 mm long acrylic adhesive tape (Nitto Denko No. 31B / acrylic adhesive) was pressed with a rubber roll onto the resin layer side of the obtained laminated film to prepare a sample. The sample was sandwiched between metal plate / rubber plate / sample / rubber plate / metal plate and left for 20 hours under a load of 2 kPa in an atmosphere of 70°C, after which it was cooled for 30 minutes or more to return to room temperature to obtain a sample for measuring peel strength. The peel strength between the acrylic adhesive tape and the laminated film of the peel strength measurement sample was measured in a thermostatic chamber at 23°C using a tensile tester (Shimadzu Corporation Autograph AGX-V) at a peel angle of 180° and a peel speed of 300 mm / min. Measurements were performed at five locations, and the average value was recorded as the measurement result.

[0075] (5) Transfer to the substrate (maximum height (Sz) of the substrate surface after peeling) An epoxy resin composition obtained by mixing 100 parts by mass of a bisphenol-type epoxy resin (jER828 manufactured by Mitsubishi Chemical Corporation), 50 parts by mass of an acid anhydride whose main component is 4-methylhexahydrophthalic anhydride (MH-700 manufactured by New Japan Chemical Co., Ltd.), and 2 parts by mass of a curing accelerator (U-CAT18X manufactured by Acid Apro Co., Ltd.) was applied to the resin layer side of the obtained laminated film using a Mayer bar so that the thickness after drying would be 20 μm, and the film was dried at 160° C. for 30 minutes to obtain a laminate in which the epoxy resin composition was laminated. Thereafter, the epoxy resin composition / laminated film was peeled off, and the maximum height (Sz) of the resin layer side of the epoxy resin composition was measured by the method described above in "(1) Flatness," and the average value was calculated. The maximum height (Sz) of the surface of the epoxy resin composition after peeling is preferably 0.40 μm or less, more preferably 0.30 μm or less, and even more preferably 0.10 μm or less.

[0076] To prepare a liquid material for forming a resin layer, an acid-modified polyolefin resin and an aqueous dispersion were produced by the following method.

[0077] <Production of Acid-Modified Polyolefin Resin A-1> 280 g of propylene-ethylene copolymer (propylene / ethylene = 99 / 1 (mass ratio)) was heated and melted in a four-neck flask under a nitrogen atmosphere, and then 32.0 g of maleic anhydride as an unsaturated carboxylic acid and 6.0 g of dicumyl peroxide as a radical generator were added over 1 hour while stirring while maintaining the temperature in the system at 170 ° C., and then reacted for 1 hour. After the reaction was completed, the obtained reaction product was poured into a large amount of acetone to precipitate a resin. This resin was further washed several times with acetone to remove unreacted maleic anhydride, and then dried under reduced pressure in a vacuum dryer to obtain an acid-modified polyolefin resin A-1 (acid modification amount 2.3%, melting point 145 ° C.).

[0078] <Production of Acid-Modified Polyolefin Resin A-2> In the production of the acid-modified polyolefin resin A-1, except that the propylene-ethylene copolymer (propylene / ethylene = 99 / 1 (mass ratio)) was changed to an ethylene-ethyl acrylate copolymer (ethylene / ethyl acrylate = 93 / 7 (mass ratio)), the same procedure as in A-1 was repeated to obtain acid-modified polyolefin resin A-2 (acid modification amount 2.0%, melting point 105°C).

[0079] <Production of Acid-Modified Polyolefin Resin A-3> 70 g of ethylene-1-octene copolymer (ethylene / 1-octene=61.9 / 38.1 (mass ratio)) and 14 g of maleic anhydride as an unsaturated carboxylic acid were dissolved in 320.4 g of xylene under a nitrogen atmosphere in a four-neck flask, and the temperature in the system was kept at 140° C. and stirring was continued. In addition, 4.2 g of dicumyl peroxide as a radical generator and 15.6 g of xylene were added to another flask to obtain a homogeneous solution, and then the system was replaced with nitrogen. A xylene solution of dicumyl peroxide was added over 30 minutes to the xylene solution in which the ethylene-octene copolymer and maleic anhydride were dissolved, and stirring was continued for 5 hours under a nitrogen atmosphere while the temperature in the system was kept at 140° C. Thereafter, the solution in the four-neck flask was cooled to 50° C., and the entire amount was poured into a large amount of methanol to precipitate a resin. This resin was further washed several times with acetone to remove unreacted maleic anhydride, and then dried under reduced pressure in a vacuum dryer to obtain an acid-modified polyolefin resin A-3 (acid modification amount 2.2%).

[0080] <Production of Acid-Modified Polyolefin Resin A-4> In the production of the acid-modified polyolefin resin A-1, except that the propylene-ethylene copolymer (propylene / ethylene = 99 / 1 (mass ratio)) was changed to a propylene-1-butene-ethylene terpolymer (propylene / 1-butene / ethylene = 64.8 / 23.9 / 11.3 (mass ratio)), the same procedure was followed as in A-1 to obtain acid-modified polyolefin resin A-4 (acid modification amount 6.3%, melting point 135°C).

[0081] Table 1 shows the structures of the obtained acid-modified polyolefin resins A-1 to A-4.

[0082] [Table 1]

[0083] <Production of Aqueous Dispersion of Acid-Modified Polyolefin Resin A-1> Using a stirrer equipped with a sealable pressure-resistant 1-liter glass container with a heater, 60.0 g of the acid-modified polyolefin resin A-1 produced by the above method, 45.0 g of ethylene glycol-n-butyl ether (boiling point 171 ° C), 6.9 g of N,N-dimethylethanolamine (boiling point 134 ° C, 1.0 times equivalent to the carboxyl group of the maleic anhydride unit in the resin), and 188.1 g of distilled water were charged into the above glass container, and the stirring blade rotation speed was set to 300 rpm and stirred. As a result, no precipitation of the resin was observed at the bottom of the container, and it was confirmed that the resin was in a floating state. Therefore, while maintaining this state, the heater was turned on after 10 minutes and heated. Then, the temperature inside the system was kept at 140 ° C and stirred for another 60 minutes. After that, the mixture was cooled to room temperature (about 25 ° C) by air cooling while stirring at a rotation speed of 300 rpm. Further, pressure filtration (air pressure 0.2 MPa) was performed using a 300 mesh stainless steel filter (wire diameter 0.035 mm, plain weave) to obtain a uniform aqueous dispersion of acid-modified polyolefin resin A-1 (solid content concentration 25% by mass). There was almost no residual resin on the filter.

[0084] <Production of Aqueous Dispersion of Acid-Modified Polyolefin Resin A-2> An aqueous dispersion of acid-modified polyolefin resin A-2 (solid content concentration: 25% by mass) was obtained in the same manner as for aqueous dispersion of A-1, except that the acid-modified polyolefin resin used was changed to A-2.

[0085] <Production of Aqueous Dispersion of Acid-Modified Polyolefin Resin A-3> Using a stirrer equipped with a 1-liter pressure-resistant glass container with a heater, 30.0 g of the acid-modified polyolefin resin A-3 produced by the above method, 90.0 g of tetrahydrofuran, 15.0 g of triethylamine, 2.4 g of 2-dimethylaminoethanol, and 165.0 g of distilled water were charged into the glass container, and the stirring blade was set to a rotation speed of 300 rpm and stirred. While maintaining this state, the heater was turned on after 10 minutes to start heating. Then, the temperature inside the system was kept at 120°C and stirred for another 60 minutes. After that, the mixture was cooled to room temperature (about 25°C) by air cooling while stirring, and the entire amount of the obtained dispersion was transferred to a 1-liter eggplant flask. The solvent was removed under reduced pressure using an evaporator while immersed in a water bath heated to 60°C, and 74 g of the aqueous medium was distilled off. Next, 93.6 g of distilled water was added to the dispersion in the recovery flask, and then the mixture was immersed in a hot water bath heated to 60° C. and the solvent was removed under reduced pressure using an evaporator to distill off 82 g of the aqueous medium. After cooling, the dispersion in the recovery flask was filtered under pressure (air pressure 0.2 MPa) with a 300 mesh stainless steel filter (line diameter 0.035 mm, plain weave) to obtain a uniform aqueous dispersion of acid-modified polyolefin resin A-3 (solid content concentration 12.5% ​​by mass).

[0086] <Production of Aqueous Dispersion of Acid-Modified Polyolefin Resin A-4> An aqueous dispersion of acid-modified polyolefin resin A-4 (solid content concentration: 25% by mass) was obtained in the same manner as for aqueous dispersion of A-1, except that the acid-modified polyolefin resin used was changed to A-4.

[0087] In order to prepare a liquid material for forming a resin layer, the following aqueous solution was used as polyvinyl alcohol (B). B-1: JT-05 manufactured by Japan Vinyl Acetate & Poval Co., Ltd. Saponification rate 94.5%, polymerization degree 500, solid content concentration 8.0% B-2: VC-10 manufactured by Japan Vinyl Acetate & Poval Co., Ltd. Saponification rate 99.3%, polymerization degree 1000, solid content concentration 8.0%

[0088] The following was used as the crosslinking agent (C). C-1: Oxazoline group-containing compound (Epocross WS-700 manufactured by Nippon Shokubai Co., Ltd., solid content concentration 25% by mass) C-2: Carbodiimide group-containing compound (Carbodilite V-02-L2, manufactured by Nisshinbo Chemical Co., Ltd., solid content concentration 40% by mass)

[0089] The following was used as compound (D). D-1: Amphiphilic oligomer (Kyoeisha Chemical Co., Ltd. Polyflow KL-900) D-2: Acetylene glycol (Olfine D-10, manufactured by Nissin Chemical Industry Co., Ltd.) D-3: Acetylene glycol ethylene oxide adduct (Olfine E1010, manufactured by Nissin Chemical Industry Co., Ltd.) D-4: Modified silicone (Kyoeisha Chemical Co., Ltd. Polyflow KL-401)

[0090] The polyethylene terephthalate constituting the base film was produced by the following method. <Polyethylene terephthalate P-1> Terephthalic acid and ethylene glycol were polymerized in the usual manner using antimony oxide as a catalyst to obtain melt-polymerized polyethylene terephthalate P-1, which was substantially free of particles. <Polyethylene terephthalate P-2> During the polymerization of P-1, silica particles having an average particle size of 2.3 μm were added in an amount of 0.08% by mass based on the polyethylene terephthalate to obtain melt-polymerized polyethylene terephthalate P-2.

[0091] Example 1 <Preparation of Liquid for Forming Resin Layer> An aqueous dispersion of acid-modified polyolefin resin A-1, an aqueous polyvinyl alcohol solution B-1, an aqueous solution C-1 of an oxazoline group-containing compound as a crosslinking agent, and a compound D-1 were mixed so that the solid contents were 100 parts by mass, 300 parts by mass, 5 parts by mass, and 20 parts by mass, respectively, and the mixture was adjusted with water to a final solid concentration of 7% by mass, thereby obtaining a liquid for forming a resin layer. <Manufacturing of laminated film> Polyethylene terephthalate P-1 was fed into extruder 1 (screw diameter: 50 mm), and polyethylene terephthalate P-2 was fed into extruder 2 (screw diameter: 65 mm), respectively, and melted at 280°C. Before reaching the outlet of the T-die, the two melts were joined and laminated in two layers so that the layer thickness ratio (P layer made of P-1 / S layer made of P-2) was 33 / 5 and the total thickness was 600 μm. The laminated melt was extruded from the outlet of the T-die of the multi-layer die, and was rapidly cooled in close contact with a casting drum by the T-die method-electrostatic pinning method, forming an unstretched film with a thickness of 600 μm. Then, this unstretched film was stretched 3.5 times with longitudinal stretching rolls heated to 90°C. A liquid for forming a resin layer having a liquid temperature of 30° C. was applied at a rate of 10 g / m 2 on one side of the longitudinally stretched film (the side of the P layer made of polyethylene terephthalate P-1) using a reverse gravure coater. 2 The longitudinally stretched film coated with the liquid for forming the resin layer was dried at 120°C and stretched 4.5 times in a transverse stretching tenter, then heat-treated at 230°C for 10 seconds, cooled, and wound up. The thickness of the obtained laminated film was 38 μm, and the thickness of the resin layer was approximately 0.10 μm. The developed interface area ratio (Sdr) of the substrate film surface not provided with the resin layer was 0.33.

[0092] Examples 2 to 19, Comparative Examples 2 to 4, 6 to 8, 10, and 12 A laminated film was obtained in the same manner as in Example 1, except that the layer structure of the base film, and the structure of the liquid material for forming a resin layer and the liquid temperature during application were changed as shown in Table 2.

[0093] Comparative Example 1 Polyethylene terephthalate P-1 was put into extruder 1 (screw diameter: 50 mm), and polyethylene terephthalate P-2 was put into extruder 2 (screw diameter: 65 mm), respectively, and melted at 280°C. Before reaching the outlet of the T-die of the multilayer die, the layers were laminated together in three layers so that the layer thickness ratio (S layer made of P-2 / P layer made of P-1 / S layer made of P-2) was 5 / 28 / 5 and the total thickness was 600 μm. The laminated melt was extruded from the T-die outlet of the multilayer die, and was rapidly cooled in close contact with a casting drum by the T-die method-electrostatic pinning method, and an unstretched film with a thickness of 600 μm was formed. Then, this unstretched film was stretched 3.5 times with longitudinal stretching rolls heated to 90°C. A laminated film was obtained in the same manner as in Example 1, except that a resin layer-forming liquid material was applied to one surface of the longitudinally stretched film.

[0094] Comparative Examples 5, 9, and 11 Except for changing the composition of the resin layer-forming liquid material as shown in Tables 2 to 4, the same procedure as in Comparative Example 1 was followed to obtain a laminated film.

[0095] Tables 2 to 4 show the results of various evaluations carried out on the laminated films obtained in the examples and comparative examples.

[0096] [Table 2]

[0097] [Table 3]

[0098] [Table 4]

[0099] The resin layers of the laminated films of Examples 1 to 19 had developed interface area ratios (Sdr) and maximum heights (Sz) within the ranges specified by the present invention, and had excellent slip properties, allowing the formation of good winding rolls, and also had flat surface shapes and good releasability.

[0100] The resin layers of the laminated films of Comparative Examples 1, 5, 9, and 11 were formed in the particle-containing S layer of the multilayered base film, and therefore the maximum height (Sz) was outside the range specified in the present invention, the flatness was poor, and the maximum height (Sz) of the adherend surface after peeling was also high. The resin layers of the laminate films of Comparative Examples 2, 3, and 10 were formed in the particle-free P layer of the multilayer base film, and had a maximum height (Sz) within the range specified in the present invention and excellent flatness. However, since they were formed by applying a resin layer-forming liquid that did not contain compound (D) or had a low content of compound (D), the developed interface area ratio (Sdr) was outside the range specified in the present invention and the films were poor in slipperiness. The resin layers of the laminated films of the other comparative examples also had Sdr and Sz outside the ranges specified in the present invention, and were therefore inferior in lubricity and flatness.

Claims

1. A laminated film having a resin layer provided on at least one surface of a base film, the particle content of the substrate film surface on which the resin layer is provided is 0.001% by mass or less; the resin layer contains an acid-modified polyolefin resin (A) and a crosslinking agent (C), the content of the crosslinking agent (C) being 1 to 20 parts by mass per 100 parts by mass of the acid-modified polyolefin resin (A); The olefin component of the acid-modified polyolefin resin (A) contains 50% by mass or more of ethylene or 70% by mass or more of propylene, A laminate film characterized in that the developed interface area ratio (Sdr) of the resin layer surface is 0.025 to 0.304%, and the maximum height (Sz) is 0.01 to 0.50 μm, as determined by a non-contact surface shape measuring device.

2. 2. The laminated film according to claim 1, wherein the olefin component of the acid-modified polyolefin resin (A) contains 1-octene.

3. 3. The laminated film according to claim 2, wherein the content of 1-octene in the olefin component is 15% by mass or more.

4. 4. The laminate film according to claim 1, wherein the peel strength between the resin layer and the epoxy prepreg is 0.5 N / cm or less when measured by attaching an epoxy prepreg to the resin layer.

5. A method for producing the laminated film according to any one of claims 1 to 4, comprising the steps of: A step of applying a resin layer-forming liquid material, the liquid material containing 100 parts by mass of an acid-modified polyolefin resin (A), 1 to 20 parts by mass of a crosslinking agent (C), and 2 to 50 parts by mass of at least one compound (D) selected from the group consisting of an amphiphilic oligomer, acetylene glycol, and an ethylene oxide adduct of acetylene glycol, and the liquid temperature being 20 to 40° C., to a substrate film; A step of drying and stretching the substrate film on which the resin layer-forming liquid has been applied; A method for producing a laminated film, comprising:

Citation Information

Patent Citations

  • Slippery polyester film and method of manufacturing the same

    JP2012020429A

  • Easily-slidable polyester film, and production process therefor

    JP2012144021A

  • Release film

    JP2015189014A

  • Laminate film

    JP2021074915A

  • Biaxially stretched polyester film for mold release

    WO2014007187A1